Investigation of MnCo2O4/MWCNT composite as anode material for lithium ion battery. Issue 8 (1st June 2019) - Kulkarni, Pranav; Ghosh, Debasis; Balakrishna, Geetha; Rawat, R.S.; Adams, S.; Reddy, M.V.
Abstract: We report a simple and scalable synthesis of MnCo2 O4 /MWCNT nanocomposite by a simple precipitation method and its application as a high capacity anode material for Li-ion batteries. X-ray diffraction analysis showed a pure phase of MnCo2 O4 and morphological analysis revealed a uniform decoration of MnCo2 O4 nanoparticles along MWCNT backbone. As an electrode material, MnCo2 O4 showed a high initial discharge capacity of 1431 mA h g −1 with a capacity retention of 444 mA h g −1 at the end of 30 cycles. With a small addition of MWCNT to MnCo2 O4, the stability of the composite increased with a reversible capacity of 871 mA h g −1 at the end of 30 cycles. The inclusion of MWCNT as a conductive matrix resulted in a significant improvement in rate capability and cyclic stability.